Time before time (2021), volume 2 ebook - Shalvey, Declan (Time Before Time (2021), 2022)
The year is 2140, and to escape a world with no future, many turn to the Syndicate, a criminal organization who, for the right price, will smuggle you back in time to a better life. After working for the Syndicate for years, Tatsuo and Oscar decide to steal one of their boss’s time machines—but soon find that the one thing you can’t run from is your past. TIME BEFORE TIME is a brand-new ongoing series where writer/artist DECLAN SHALVEY (BOG BODIES) joins forces with the WRITE IT IN BLOOD team of RORY McCONVILLE and JOE PALMER.